Optimizing English Writing Skills Using the Suggestopedia Method Assisted by Paper Craft Media - Sholihah, Husna Imro'athush; Rofiq, Muhammad Aunur; Kurniawan, Wildan Farih; Kamila, Azila Rahma (English Education Department at FKIP Nommensen University, 2025)
This research aims to optimize students' English writing skills by applying the Suggestopedia method in conjunction with papercraft media. Writing skills often pose a challenge for students, particularly due to limitations in vocabulary, ideas, and motivation. The Suggestopedia method, which emphasizes a relaxed and enjoyable learning atmosphere, was chosen because it can reduce learning anxiety and encourage free expression. Meanwhile, papercraft media is used as a visual and kinesthetic aid to stimulate creativity and facilitate the development of ideas in writing. This research employs an experimental method with control and experimental classes involving students from STKIP Muhammadiyah Blora. The sample of this study are 30 students. Data collection techniques use tests and questionnaires. The results indicated a significant improvement in the experimental group (t(29) = 12.54; p < 0.001) compared to the control group (t(29) = 6.87; p < 0.001), with an average gain of 34.09% versus 15.89%. The questionnaire results revealed that 90% of students felt more confident in writing, and 85% stated that papercraft helped them develop ideas more easily. In conclusion, integrating Suggestopedia with papercraft provides an effective, engaging, and motivating approach to improving students’ English writing skills.